ANALISIS KUALITAS PELAYANAN DAN NILAI EMOSIONAL TERHADAP KEPUASAN KONSUMEN (STUDI PADA KONSUMEN HOTEL EMERALD GARDEN MEDAN) - Rahmadany Lubis, Dilla; Hafriz Rifki Hafas (Universitas Harapan Medan, 2025)
This research was motivated by the growth of Emerald Garden Medan hotel which began to decline. This causes hotels in the city of Medan to be able to develop offerings in various aspects in order to increase hotel visits and provide optimal satisfaction for consumers. One of the conditions for a hotel to be successful in future competition is to strive to achieve its goals by creating and retaining customers. The role of hotels as a suggestion is to meet consumer needs is becoming increasingly important to society. This study aimed to test whether service quality, emotional value has an effect on customer satisfaction either partially or simultaneously at the Emerald Garden Medan Hotel. The population in this study amounted to 100 respondents with the sampling technique of Accidental Sampling. The analysis technique used is multiple linear regression. The results showed that service quality had a positive and significant effect on customer satisfaction at Emerald Garden Hotel Medan, emotional value had a positive and significant effect on customer satisfaction at Emerald Garden Hotel Medan. Service quality and emotional value have a positive and significant effect simultaneously on customer satisfaction at Emerald Garden Hotel Medan.